Inhibitory neuron map of sevoflurane induced neurotoxicity model in young primates - Niu, Yixuan; Cheng, Yanyong; Miao, Zhengjie; Xu, Jinnan; Jiang, Hong; Yan, Jia (Frontiers in Cellular Neuroscience, 2023)
Introduction: Sevoflurane, one of the most commonly used anesthetic agents in children, may induce neuronal dysfunction and cognitive impairment. Exposure to sevoflurane might induce an imbalance between neural excitation and inhibition which could be a mechanism behind anesthesiainduced cognitive and affective dysfunctions. However, the underlying mechanisms remain unclear.In this study, we used two rhesus macaques in the control group, and one rhesus macaques in the anesthesia group. We employed single-nucleus RNA sequencing (snRNA-seq) technology to explore alterations in distinct types of inhibitory neurons involved in the long-term cognitive impairment caused by sevoflurane in young macaques.Results: Following sevoflurane treatment, an upregulation was observed in the SST+ inhibitory neuron in the LHX6+ neighborhood in the hippocampus of rhesus macaques. This alteration might impact brain development by influencing interneuron migration and maturation. Additionally, we proposed a novel classification of inhibitory neurons, defined by CNR1 and LHX6 applicable to both humans and macaques.Discussion: Our study proposed a novel classification of inhibitory neurons defined by LHX6 and CNR1, relevant in macaques and humans. We also provide evidence that sevoflurane upregulated the SST+ inhibitory neuron in the LHX6+ neighborhood in the hippocampus of rhesus macaques, which may underlie the potential neurotoxic effects induced by general anesthetics. Our results also offer a more reliable approach for studying the structure and function of the human brain.